The global corporation and its role as a source of innovation for sustainable development : beyond corporate social responsibility - Gonzalez, Maria Susana Muhamad; Hamann, R.; Loorbach, D. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.